Antropologia i ascetyzm - Doroszkiewicz, Warsonofiusz (Elpis, 2014)
Socrates described man as a soul imprisoned in the body, whereas the soul is in him that something which participates most in the divine nature, something that governs us. The Bible though sees a man as a complete whole, in which the soul, the spirit and the body are described as certain aspects of the functioning of this whole, and not its autonomous parts. A man is also understood as predestined by God to be saved thanksto the redemptory mission of the Messiah – Jesus Christ. Apostle Paul introduces the idea that a man consists of the body, the spirit and thesoul. Human soul, due to the inherited results of the original sin, is ina permanent danger of the evil temptations. The key to its health is themind which enables the man to know God, the interior sense of thethings and the principles of created things. The mind tends to God,it can purify itself of the evil and introduce and maintain the holiness coming from God. The Fathers of the Philocalia considered the heart asthe spiritual centre of the human person directly engaged in the spiritual warfare, and its purification considered as an indispensable condition of man’s transformation. God loves man, He created him on His image, gave him freedom and calls him unceasingly to the completion of the divine likeness – that is to the natural participation in the divine life. During the earthly life this participation is attained by a slow process of elevation aboveone’s own limits and opening oneself to the action of the uncreatedenergies of God. This process implies the purification of the hole humanbeing by an ascetic effort in order to overcome the sinfulness. Ascesis inChristianity is understood as a practice of renouncements, aiming at thespiritual freedom of any disordered attachement to the created reality.Monastic ascesis is a complete renouncement, a constant crucifying ofoneself in order to fight with the passions, to keep God’s commandmentsand to acquire virtues. This ascesis had different forms, of which themost important and significant is the practicing of the “pure prayer”,“the prayer of the heart” which helps a man to purify himself of thepassions and acquire the knowledge of God, the ultimate peace and the contemplation of God.